Dança do Ventre: técnica, expressão e significados: uma etnografia nas Escolas de dança em Pelotas/RS - Oliveira, Eugênia Squeff de (2011)
Belly dancing is understood as art and tradition of the Arabian culture, but practiced beyond it s places of origin. Among its adepts are people from varied ethnic groups and cultures. In this study we investigate the meanings of belly dancing among teachers and students of dancing schools in the city of Pelotas (Brazil) which offer the practice, as well as the meanings shared by the public which appreciates the dance. Comprehension was sought, through observation of the practices and the by the capture of meanings present in the social imaginary, of how this dance is being represented in the pelotense society, how this art s transmission, its transformation and itsadaptation to various cultures takes place